2021
DOI: 10.1210/clinem/dgab346
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gut Microbiota during Early Pregnancy with Risk of Incident Gestational Diabetes Mellitus

Abstract: Aims We aimed to assess the association between gut bacterial biomarkers during early pregnancy and subsequent risk of gestational diabetes mellitus (GDM) in Chinese pregnant women. Methods Within the Tongji-Shuangliu Birth Cohort study, we conducted a nested case-control study among 201 incident GDM cases and 201 matched controls. Fecal samples were collected during early pregnancy (at 6-15 weeks), and GDM was diagnosed at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…Maternal obesity during pregnancy may also increase this bacterium ( 33 ). Another pregnancy cohort study revealed that the abundance of Staphylococcus relative to Clostridium, Roseburia , and Coriobacteriaceae were positively correlated with fasting blood glucose ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal obesity during pregnancy may also increase this bacterium ( 33 ). Another pregnancy cohort study revealed that the abundance of Staphylococcus relative to Clostridium, Roseburia , and Coriobacteriaceae were positively correlated with fasting blood glucose ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a few data have demonstrated that Parasutterella actively participates in metabolic functionality, particularly the deconjugation process of taurine-conjugated bile acids [ 26 ], while Turicibacter had a beneficial role in host serotonin metabolism [ 27 ]. It has been shown that Adlercreutzia has an inverse correlation with cardiovascular functions [ 28 ], diabetes [ 29 ], and gestational diabetes mellitus (GDM) [ 30 ], which regulates phytoestrogenic activity, produces short-chain fatty acids (SCFAs), and has neuroprotective effects. In line with our study, increasing studies on human MS have indicated that individual or combined strains of Prevotella may have anti-inflammatory and neuroprotective effects [ 20 ], through enhancing the production of protective SCFAs [ 31 ], increasing the production of phytoestrogens [ 32 ], and mediating Th17-related immune responses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genus Ruminococcus was observed to be less abundant in humans taking rich-vegetable diets [ 41 ], and was consistently associated with an increased risk of T2DM [ 34 ]. Genus Adlercreutzia was less abundant in gestational hypertensive women taking higher dietary fiber [ 42 ], but more prevalent in healthy controls than patients with diabetes [ 43 ] and gestational diabetes [ 44 ]. Genus Prevotella was also a detrimental bacterium linked to chronic systemic inflammation [ 45 ] and dominated dysbiosis in T2DM patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%